AKTIVITAS ANTIOKSIDAN KOMBINASI EKSTRAK ETANOL 70% DAUN MELINJO (Gnetum gnemon L.) DAN BUAH BELIMBING WULUH (Averrhoa bilimbi L.) - Faujiah, Sifa; Sumiati, Triyani; Sulastri, Lilik (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Melinjo leaves (Gnetum gnemon L.) and Star Fruit (Averrhoa bilimbi L.) is a plant that can be used as traditional medicine. Melinjo leaves contain alkaloids, saponins, tannins, phenols, flavonoids, triterpenoids and steroids. Star fruit contains alkaloids, flavonoids and triterpenoids. These compounds function as antioxidants to counteract free radicals. The purpose of this study was to determine the secondary metabolites and determine the antioxidant activity of the combination of 70% ethanol extract of melinjo leaves and star fruit. The simplicia powder was extracted by maceration using 70% ethanol solvent, then a phytochemical test was carried out, after which the single antioxidant test and the combination of extracts were tested at a ratio of 1:3, 3:1, 1:1 with concentration series 5, 10, 20, 40, 80 ppm, the determination of antioxidants was carried out using DPPH (1,1-diphenyl-2-picrylhydrazyl) by measuring the absorbance of DPPH at a wavelength of 515 nm. The results of this study indicate that the value of IC50 for the ethanol extract of melinjo leaves was 7.86 μg/mL, the ethanol extract of star fruit was 33.70 μg/mL and the IC50 value from each combination of ethanol extract of melinjo leaves and star fruit at a ratio of 1:3 obtained 32.1 μg/mL, a ratio of 3:1 obtained 5.91 μg/mL and a ratio of 1:1 obtained 19.49 μg /mL. Based on the results of the study, it can be concluded that the antioxidant activity of the combination of 70% ethanol extract of melinjo leaves and star fruit in a ratio of 3:1 has an IC50 value the best was 5.91 μg/mL which was included in the very strong category. Keywords: Antioxidants, Melinjo Leaves, Star Fruit, Phytochemicals, DPPH